The Use Of Games In Teaching Vocabulary In Young Learners - Raihan, Fairuz Dewi (Prosiding University Research Colloquium, 2021)
The purpose of this paper is to discuss the possibilities of improving the English vocabulary mastery for young learners through the use of games. Several approaches and methods can be used to teach English vocabulary to young learners. The method we use to collect information in making this journal is review articles, we use the journal as a reference. One good way to learn vocabulary is to use real objects that children can visualize later. They need to pay attention to learning to use words and repeating them too. The other method is the direct method where there is no translation and the use of the mother tongue is prohibited. The games used by the teacher to teach words to young learners are hot potato game, memory challenge, last one standing, pictionary, bingo. From the application of the game, young learners can quickly and easily increase their English vocabulary.